Non-mastoidectomy Cochlear Implant Approaches: A Literature Review - El-Anwar,Mohammad Waheed (2016)
Abstract Introduction Posterior tympanotomy approach for cochlear implant (CI) surgery, has been the most commonly used worldwide with current 0.7% rate of facial nerve injury. Non-mastoidectomy CI approaches include the suprameatal approach (SMA) and its modifications, the transcanal approach and its modifications and the pericanal approach for electrode insertion. Objectives The objective of this study was to review the literature regarding nonmastoidectomy CI approaches. Data Synthesis A search was performed in the LILACS, MEDLINE, SciELO, PubMed databases and Cochrane Library in February 2015, and the key words used in the search were CI, SMA, transcanal approach, pericanal approach, or electrode extrusion. About 30 studies that met the criteria described in "Study Selection" were read in full. The studies showed 1014 patients that underwent CI by SMA or its modifications, 266 CI patients treated by transcanal approach or its modifications, and 15 patients implanted by the pericanal approach. Reported complication with SMA was 99 (9.8%) minor and 13 (1.3%) major. With transcanal, there were 24 complications; 19 (7.1%) minor and 5 (1.9%) major. No post-operative complication was reported in pericanal approach. Studies showed no reported facial nerve paresis or paralysis in all non-mastoidectomy approaches. Conclusion Complications rates with non-mastoidectomy approaches are similar to those found in the mastoidectomy approach. Thus, non-mastoidectomy approaches may be an alternative in cases where the conventional mastoidectomy approach is difficult to perform. It would be helpful for CI surgeons to become familiarized with these approaches.